TASK-BASED LANGUAGE TEACHING IN ESP CLASSROOMS AT TECHNICAL COLLEGES: DEVELOPING COMMUNICATIVE COMPETENCE FOR PROFESSIONAL CONTEXTS - Parmonova Muxlisa Bozorovna, (TADQIQOTLAR, 2026)
Abstract:  This  article  investigates  the  application  of  Task-Based  Language Teaching (TBLT) methodology within English for Specific Purposes (ESP) instruction at technical colleges in Uzbekistan. The study examines how professionally oriented communicative  tasks  simultaneously  advance  language  competence  and  vocational readiness  among  second-year  technical  students.  Drawing  on  empirical  evidence gathered  over  one  full  academic  semester,  the  paper  demonstrates  that  carefully designed  tasks  grounded  in  students'  anticipated  occupational  activities  produce measurable gains in productive language skills and communicative performance while meaningfully heightening learner motivation.